PENERAPAN MODEL PEMBELAJARAN GALLERY WALK DAN MEDIA KOKAMI (KOTAK KARTU MISTERI) UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI SISWA KELAS XI DI SEKOLAH MENENGAH ATAS NEGERI 10 BOGOR - Indri Yani; Engkus Kusmana (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2020)
THEAPPLICATION OF GALLERY WALK MODEL AND KOKAMI MEDIA TO IMPROVE STUDENTS’ ACHIEVEMENT IN BIOLOGY ON ELEVENTH GRADE STUDENTS IN SEKOLAH MENENGAH ATAS NEGERI 10 BOGORThis research is a Classroom Action Research (CAR) which aimed at to improve students’ achievement in biology using gallery walk model and mystery cards box. The samples are 35 students of the eleventh grade IPA 2. This research was done in two cycles, with each cycles consist of two meetings. There are four stages for each cycles, they are planning, treatment, observation, and reflection. Evaluation is given at the end of every cycles using calibrated instrument. The evaluation result on the first cycle is 74,48 there are 24 students reach the maximum mastery criteria with KKM achievement percentage around 68,57% from 35 students, and on the second cycle the average score increased into 81,45 with KKM achievement percentage at 82,85%. It shows that the application of gallery walk learning model and Kokami media can improve students’ achievement of the eleventh grade IPA 2 in biology subject in SMAN 10 Bogor.